2019
DOI: 10.1111/jan.13973
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of a STOMA psychosocial intervention programme for colorectal cancer patients with stomas

Abstract: Aims To evaluate preliminary effects of a newly developed STOMA psychosocial intervention programme that was delivered via a multi‐modal and multi‐dimensional approach on the improvement of outcomes of colorectal cancer patients with stoma. Background With a distorted body image and the loss of an essential body function, stoma patients face difficulties in everyday life in terms of physical, psychological, and social aspects. Few studies have explored effects of psychosocial interventions on improving stoma‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 18 publications
1
45
0
2
Order By: Relevance
“…This suggests that patients' compliance with the stoma and their quality of life are more affected in the first weeks. The findings are also consistent with previous findings that specialist stoma nurses' support and education contributed significantly to positive adjustment in ostomy patients 14,23,24 .In the literature, there is an test study conducted by Zhang et al in which patients were called and followed by stoma care nurses in the first three months after the stoma opening; however, there is no study in which no phone counselling service they could call any time they encounter a problem 14 . This study revealed the importance of phone counselling in patients with intestinal stoma after the discharge.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests that patients' compliance with the stoma and their quality of life are more affected in the first weeks. The findings are also consistent with previous findings that specialist stoma nurses' support and education contributed significantly to positive adjustment in ostomy patients 14,23,24 .In the literature, there is an test study conducted by Zhang et al in which patients were called and followed by stoma care nurses in the first three months after the stoma opening; however, there is no study in which no phone counselling service they could call any time they encounter a problem 14 . This study revealed the importance of phone counselling in patients with intestinal stoma after the discharge.…”
Section: Discussionsupporting
confidence: 89%
“…It is stated in the literature that one of the most important problems experienced by individuals with stoma is the smell and patients also experience skin problems. In addition, studies have revealed that patients' bathing, nutrition, and sleep habits change and the problems they experience on this topic are emphasized [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . In this study, in the weeks 1-6 individuals were observed to have mostly physiological problems such as leakage, skin ulcerations, gas and smell.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotherapeutic interventions have been described in CRC population, mainly in patients with newly-formed stomas, with generally satisfactory effects. Stoma patients, due to a distorted body image and the loss of an essential body function, face difficulties in everyday life in terms of physical, psychological, and social aspects [ 107 ]. One of the most common psychosocial intervention described in this population is preoperative education, which appears to satisfactorily reduce both LOS and days to stoma proficiency [ 108 , 109 ].…”
Section: Multidisciplinary Team and Comprehensive Interventions In Colorectal Cancer Patientsmentioning
confidence: 99%
“…The care needs and abilities of the caregivers of permanent enterostomy are easily ignored by the medical staff, and the care process may lack standardization and professionalism. In recent years, scholars at home and abroad have gradually shifted their research focus from cancer patients to caregivers, but few are involved in the intervention research of caregivers' care needs, especially the caregivers of permanent enterostomy patients (Griffin et al., 2014; Kim & Carver, 2012; Lim et al., 2019). Through literature review, intervention research mainly comprised group education, ostomy clubs, and focused solution modes; the process of education intervention lacked stage and effectiveness, and the intervention mainly occurred in the hospital (Karabulut et al., 2014; Millan et al., 2010; Sweeney‐Magee et al., 2020).…”
Section: Introductionmentioning
confidence: 99%